High density lipoprotein-associated proteins in non-obese women with and without polycystic ovary syndrome - Butler, Alexandra E.; Moin, Abu Saleh Md; Reiner, Željko; Sathyapalan, Thozhukat; Jamialahmadi, Tannaz; Sahebkar, Amirhossein; Atkin, Stephen L. (Frontiers in Endocrinology, 2023)
Introduction. Dyslipidemia frequently occurs in women with polycystic ovary syndrome (PCOS), but it is unclear whether dyslipidemia is due to obesity and insulin resistance (IR) or is inherent to PCOS. To address this, proteomic analysis of proteins important in lipid metabolism, particularly for high-density lipoprotein cholesterol (HDL-C), was performed in non-obese, non-insulin resistant PCOS women compared to matched controls. Methods. Weight and aged-matched non-obese subjects with PCOS (n=24) and without IR were compared with control women (n=24). 19 proteins were measured by Somalogic proteomic analysis: alpha-1-antichymotrypsin, alpha-1-antitrypsin, apolipoproteins A-1, B, D, E, E2, E3, E4, L1, M, clusterin, complement C3, hemopexin, heparin cofactor-II (HCFII), kininogen-1, serum amyloid A-1, amyloid beta A-4 and paraoxonase-1. Results. Women with PCOS had a higher free androgen index (FAI) (p<0.001) and anti-Mullerian hormone (AMH) (p<0.001), but IR and C-reactive protein (CRP), a marker of inflammation, did not differ from controls (p>0.05). The triglyceride:HDL-cholesterol ratio was elevated (p=0.03) in PCOS. Alpha-1-antitrypsin levels were lower (p<0.05) and complement C3 levels were higher (p=0.001) in PCOS. C3 correlated with body mass index (BMI) (r=0.59, p=0.001), IR (r=0.63, p=0.0005) and CRP (r=0.42, p=0.04) in women with PCOS, though no correlations of these parameters with alpha-1-antitrypsin were found. Total cholesterol, triglycerides, HDL-cholesterol, LDL-cholesterol and levels of the other 17 lipoprotein metabolism-associated proteins did not differ between the two groups (p>0.05). However, in PCOS, alpha-1-antichymotrypsin correlated negatively with BMI (r=-0.40, p<0.04) and HOMA-IR (r=-0.42, p<0.03), apoM correlated positively with CRP (r=0.36, p<0.04) and HCFII correlated negatively with BMI (r=-0.34, p<0.04). Conclusion. In PCOS subjects, when obesity, IR and inflammation confounders were absent, alpha-1-antitrypsin was lower and complement C3 was higher than in non-PCOS women, suggesting increased cardiovascular risk; however, subsequent obesity related IR/inflammation likely stimulates other HDL-associated protein abnormalities, thus increasing cardiovascular risk further.